Aesthetic values of the decorations heterogeneities in Islamic architecture: وسام كامل عبد الامير، أشرف كامل عبد الامير (Al-Academy, 2015)
Covariance technique represents a design to bring out the decorative components And organized in unfamiliar a manner Turn to custom patterned to make a qualitative difference in the pattern of the general composition of the implicit overall,question research problem emerges Based on the above, (Is the aesthetic values of the property heterogeneities in Islamic architecture configurations decorations?). Detect it through the knowledge of the species and decorative components containing heterogeneities And his methods within each of Iraq and Iran and theoretical framework try to monitor the opinions and threads aesthetic perception in the Islamic and Construction decorative art formations in Islamic architecture and features of heterogeneities in Islamic decorative art, and The measures included the research community involved (51) and We selected (4) Samples, Been analyzed in the light of the form presented to the experts to demonstrate its sincerity and persistence.the most important result of The search is Aesthetic values of the property variation across overlapping themes and decorative realism within a holistic unit within the General Layout and Impact on the functional aspect and decorative in Islamic architecture Which is reflected in a superficial manner (self-beauty) components derived from nature or modified them , In conscious way (objective beauty) Denote the components of the congruent with the Islamic faith And their ability to show aesthetic yield ,while The types and decorative components are included covariance structure to achieve the goals of aesthetic represented by (plant ornament) and Built- with derivative frilly animal nature , And (linear ornament) By integrating twigs plant With linear motifs in a single structure, the And (geometric ornament) That rely two different forms to make a composition built through interdependence with plant motifs ,This was done by changing the most important methods for modification and conversion and condensation and phenotypic integration and substitution